2022
DOI: 10.3389/fimmu.2022.1025861
|View full text |Cite|
|
Sign up to set email alerts
|

Bibliometric and visual analysis of neutrophil extracellular traps from 2004 to 2022

Abstract: BackgroundNeutrophil extracellular traps (NETs) are specialized structures formed by neutrophils that were initially found to be important in killing pathogenic bacteria during infection. With the development of related research, the relationship between NETs and diseases such as sepsis, cancer, and systemic lupus erythematosus has received close attention. However, there is a lack of reports that comprehensively and objectively present the current status of NETs-related studies. Therefore, this study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…The bibliometric analysis in this study utilized four tools: the 'bibliometrix' R package, 12 the bibliometric online analysis tool (www.bibliometric.com), CiteSpace 6.2.R4 12 , and VOSviewer 1.6.19. 12 Bibliometrix, developed by Italian professor Massimo Aria and colleagues, is a comprehensive bibliometric software package used for analysis and visualization in R. 13 This package enables data gathering and analysis of publication and citation counts for countries, institutions, journals, and authors. The 'Remap' package in R is employed to illustrate the distribution of research articles on world maps.…”
Section: Data Analysis and Visual Network Analysismentioning
confidence: 99%
“…The bibliometric analysis in this study utilized four tools: the 'bibliometrix' R package, 12 the bibliometric online analysis tool (www.bibliometric.com), CiteSpace 6.2.R4 12 , and VOSviewer 1.6.19. 12 Bibliometrix, developed by Italian professor Massimo Aria and colleagues, is a comprehensive bibliometric software package used for analysis and visualization in R. 13 This package enables data gathering and analysis of publication and citation counts for countries, institutions, journals, and authors. The 'Remap' package in R is employed to illustrate the distribution of research articles on world maps.…”
Section: Data Analysis and Visual Network Analysismentioning
confidence: 99%
“…Article co-citation analysis expresses the relationship between articles by analyzing the co-citation frequency of references. [28] When certain articles and journals are repeatedly quoted, the knowledge carriers cited are essentially recognized by the scientific community in which it is found, thus creating a scientific paradigm. [29] This paradigm relationship is visualized through Citespace to form a co-citation network that can reflect the knowledge base and research frontiers of an academic field.…”
Section: Highly Cited Publications and Referencesmentioning
confidence: 99%
“…The process of releasing NETs from the cell is called NETosis. Depending on the activator, NETosis can be lytic and results in the death of the neutrophil (classical pathway) or non-lytic, in which NETs are released as vesicles and the cell retains its primary functions (Brinkmann et al, 2004;Kenny et al, 2017;Wan et al, 2022). Linhares-Lacerda et al (2020) reported that NETs are also a carrier of miRNAs.…”
Section: Neutrophil Extracellular Traps (Nets) and Mirnamentioning
confidence: 99%